Application of Statement of Accounting Standards (PSAK) No. 45 on the Financial Statements of Yayasan Cendekia Maluku - Loilatu, Sahlan; Kainama, Maryoni Stevanny; Tomasoa, Theodora F. (Journal Of Accounting Management Business And International Research, 2022)
The Foundation obtains resources to carry out its operational activities from non-binding revenues. Therefore, transparency, accountability, and accountability for resource management are demanded. The accountability report is a financial report. A good and correct financial report is in accordance with generally accepted SAK. SAK which regulates the preparation and presentation of financial statements of non-profit entities is PSAK No. 45. Applying PSAK No. 45, it is hoped that the Maluku Cendekia Foundation can manage financial information professionally. The purpose of this research is to find out how to apply the preparation and presentation of financial statements based on PSAK No. 45. Type of research used is descriptive qualitative research. Data were obtained by means of observation, interviews, and document studies at the Cendekia Maluku Foundation. the data obtained are primary and secondary data, the premier data is obtained through a statement from the head of the foundation's finance, while the secondary data is in the form of the foundation's financial report in 2021. The results of the study show that the Maluku Cendekia Foundation has not implemented PSAK No. 45 in its financial reporting. the format for the preparation of the three types of reporting presented is in accordance with PSAK No. 45. The financial statements of the foundation only contain three types of financial reporting, statements of financial position, activity reports and cash flow statements. The notes to the financial statements are not included because the foundation only requires three financial reports. in some financial statements also do not contain some important material such as, the cash flow statement does not contain cash flows from investing activities.